The Pathogenesis and Differential Diagnosis of Acute Respiratory Distress Syndrome Induced by Direct and Indirect Etiological Factors - V. V. Moroz; A. V Vlasenko; A. M Golubev; V. N. Yakovlev; V. G. Alekseyev; N. N. Bulatov; T. V. Smelaya (Общая реаниматология, 2011)
Objective: to study the specific features of the mechanisms responsible for the development of acute respiratory distress syndrome (ARDS) induced by direct and indirect damaging factors and to reveal its differential diagnostic signs. Materials and methods. Lung morphological changes were studied creating experimental models of ARDS of various genesis in 75 outbred male albino rats weighing 300—400 g, which included the direct damaging factor acidine-pepsin aspiration (Group 1, n=25) and the indirect damaging factor blood loss (Group 2, n=50). Prospective examinations were made in 73 patients (43 men and 30 women, whose age was 21 to 69 years) with ARDS caused by direct damaging factors, such as aspiration pneumonitis, pneumonia, blunt chest injury, and pulmonary contusion (37 patients, including 21 men and 16 women) and in those with ARDS caused by indirect damaging factors, such as abdominal sepsis, severe concomitant injury, and hemorrhagic shock (36 patients, including 22 men and 14 women). Results. The study has shown that ARDS caused by direct and indirect damaging factors is characterized by different developmental mechanisms and lung morphological changes that underlie the specific features of functional impairments. Conclusion. The findings made it possible to substantiate and propose new approaches to the differential diagnosis and treatment of ARDS caused by direct and indirect damaging factors. Key words: acute respiratory distress syndrome, direct and indirect damaging factors, thoracic and pulmonary compliance, lung extravascular fluid, positive end-expiratory pressure, respiratory support, intensive care unit.